Multifractal dimension spectra in polymer physics - von Ferber, Ch.; Holovatch, Yu. (Condensed Matter Physics, 1999)
We study the multifractal properties of diffusion in the presence of an absorbing polymer and report the numerical values of the multifractal dimension spectra for the case of an absorbing self avoiding walk or random
walk. Досліджені мультифрактальні властивості дифузії поблизу фрактального (полімерного) абсорбера та приведені числові значення спектру мультифрактальних вимірностей для випадку абсорбера у вигляді блукань із самоуниканням та випадкових блукань.